PENERAPAN SISTEM BAGI HASIL PADA PETANI KARET PERSPEKTIF EKONOMI ISLAM - Tezi Asmadia; Yolaisa Yolaisa (Saqifah: Jurnal Hukum Ekonomi Syariah, 2022)
The purpose of this study was to determine the application of the rubber farmers' profit sharing system in Dharmasraya Regency and to find out the Islamic economic review of the application of the rubber farmers' profit sharing system. Data collection techniques used are interviews and documentation. From the research that has been done, it can be concluded that the application of the profit-sharing system to rubber farmers uses a ratio of 50:50, meaning that 50% is for rubber plantation owners and 50% is for rubber tappers. because the garden owners bear the full maintenance costs and they only use the services of rubber farmers to tap their gardens. And in setting the selling price, they refer to the standard market price in the local area, this closes the opportunity for rubber farmers to exploit, because they cannot determine the price personally. If judged from the point of view of Islamic economic studies, the application of the profit-sharing system for rubber plantations in Jorong Kampung Baru Nagari Koto Salak, Dharmasraya Regency, is in accordance with Islamic economics.